Juridical Review of Gambling Crimes - Prisca Herdian Prastika (Proceedings Series on Social Sciences & Humanities, 2023)
The phenomenon of gambling is a form of game using bets that are fortuitous in nature. Gambling phenomenon is a form of game using bets that are fortuitous, to get a win it also requires playing skills are also required. Gambling in the historical process has not been easy to eradicated, although reality also shows that the gambling proceeds obtained by the government can be used for development efforts. Obtained by the government can be used for development efforts. But apart from that, the negative impact of gambling is greater than the positive impact. its positive impact. Criminal law is often used to solve social problems, especially in crime prevention. Especially the problem of gambling as a form of community disease. This research aims to examine the regulation of the prohibition of gambling in the Indonesian legal system and the application of the Indonesian legal system to gambling. The type of research that will be used by the author is normative juridical research. Normative juridical research is normative juridical research is research conducted using the library method and which bases its analysis on the applicable laws and regulations that are relevant to the legal issues that are the focus of the research. The focus of the research. By using normative juridical research, the author can find legal arrangements for gambling crimes in the Criminal Code regulated in Article 303 and Article 303 bis and further strengthened by Law No. 7 of 1974 concerning Gambling Control, which is conventional gambling. Meanwhile, unconventional gambling is a new type that has developed and is regulated by Law No. 11 of 2008 concerning Electronic Information and Transactions, namely in Article 27 paragraph (1) and Article 45 paragraph (1). The application of Articles 426 and 427 of the Criminal Code only covers gambling offenses that occur within the territory of the Republic of Indonesia.